2013
DOI: 10.1159/000345987
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Markers of Motor and Nonmotor Features of Parkinson's Disease: An [<sup>18</sup>F]Fluorodeoxyglucose Positron Emission Computed Tomography Study

Abstract: Aim: We sought to identify markers of motor and nonmotor function in Parkinson's disease (PD) using advanced neuroimaging techniques in subjects with PD. Methods: We enrolled 26 nondemented PD subjects and 12 control subjects. All subjects underwent [18F]fluorodeoxyglucose positron emission computed tomography (FDG-PET) and magnetic resonance imaging, and a complete neuropsychological battery. Results: FDG-PET of subjects with PD revealed significant metabolic elevations in the bilateral posterior l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 118 publications
(78 reference statements)
3
82
0
3
Order By: Relevance
“…Studies using T1‐weighted imaging reported reduced GM thickness in the temporal lobes 62 or increased atrophy in the frontal and parietal lobes (e.g. bilateral precentral gyri, right precuneus and posterior cingulate cortex), insula 63 and left nucleus accumbens 65 to be correlated with apathy, although this was not replicated in other studies 14, 64. The only study using DTI to examine the neural substrates of apathy in PD did not observe any difference in white matter integrity between patients with apathy and those without apathy and HCs 65.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…Studies using T1‐weighted imaging reported reduced GM thickness in the temporal lobes 62 or increased atrophy in the frontal and parietal lobes (e.g. bilateral precentral gyri, right precuneus and posterior cingulate cortex), insula 63 and left nucleus accumbens 65 to be correlated with apathy, although this was not replicated in other studies 14, 64. The only study using DTI to examine the neural substrates of apathy in PD did not observe any difference in white matter integrity between patients with apathy and those without apathy and HCs 65.…”
Section: Methodsmentioning
confidence: 84%
“…However, positive correlations between apathy and prefrontal, temporal, parietal and limbic areas were also noted in some studies 14, 56, 57, 58. Studies using T1‐weighted imaging reported reduced GM thickness in the temporal lobes 62 or increased atrophy in the frontal and parietal lobes (e.g.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…2 Several functional imaging studies 94,95 in patients with Parkinson's disease without dementia have supported this hypothesis, showing that these patients can present with abnormal activation at the level of the dorsolateral or ventrolateral prefrontal cortex and caudate nucleus during executive tasks. Results from glucose metabolism studies [96][97][98] with ¹⁸F-FDG PET in Parkinson's disease have shown that apathy severity is associated with metabolic activity in diff erent cognitive regions, including the inferior medial frontal gyrus, cingulate cortex, insula, cuneus, and tempo roparietal region.…”
Section: Lesions and Neuroimagingmentioning
confidence: 99%
“…Parkinsonizm sendromlarında beyin FDG PET görüntüleme saptanan anormal bulguların yaygınlığı ve derecesi klinik bulgular ile genellikle korelasyon gösterir (1,3,19,23,24,30,34,35,39,49,50,51,52). PH için klinik belirtiler ile ilişkili özgül metabolik tutulum biçimleri bulunur: Örneğin; tremor ile ilişkili serebellotalamo-kortikal yolakların etkilendiği (23,31,53); motor belirtiler ile ilişkili olarak putamen ve premotor korteksi içine alan (19,50,52,53); bilişsel bozukluklar ile ilişkili olarak da frontal ve parietal asosiyasyon alanlarında hipometabolizma ve serebellumda hipermetabolizma ile karakterize özgül metabolik ağ yapıları tanımlanmıştır (53,54).…”
Section: Beyin Fluorodeoksiglukoz Pozitron Emisyon Tomografisibulgularıunclassified